Processos de pensamentos ativados na resolução de tarefas matemáticas Standards e Não Standards - das Flôres, Aparecido Alves (2022)
For the study that we bring up, we have raised the following research question: Which thought processes are activated by students while solving standard and non-standard mathematical tasks? In order to answer this question, we have analyzed secondary school students’ answers to two tests consisting in standard and non-standard tasks. The research assembles data of students enrolled in the Building Technician course offered by the Professional Education Territorial Center (CETEP), situated in the backland of Bahia, Brazil. Within a qualitative, descriptive approach, we analyzed the data according to cognitive and metacognitive references about students’ behavior while solving mathematical problems. We organized the protocols of answers to the tests in categories of activated thought processes, namely: poor, rich, very rich, confuse and blank. Upon the conclusion of our analysis, we noticed that most students present poor thought processes for both types of tasks, using a few cognitive and metacognitive strategies. We have deduced that students are more accustomed to solving standard tasks than non-standard ones, since they showed some thought rigidity while solving questions that were out of their school routine.